2018
DOI: 10.1186/s12888-018-1663-5
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of brief psychological interventions for suicidal presentations: a systematic review

Abstract: BackgroundEvery year, more than 800,000 people worldwide die by suicide. The aim of this study was to conduct a systematic review of the effectiveness of brief psychological interventions in addressing suicidal thoughts and behaviour in healthcare settings.MethodsFollowing PRISMA guidelines, systematic searches were conducted in MEDLINE, CINAHL, EMBASE, the Cochrane Central Register of Controlled Trials and PsycINFO databases. A predefined search strategy was used. Two independent reviewers screened titles and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 26 publications
5
66
0
Order By: Relevance
“…Researchers can investigate the SHORES mnemonic by comparing its factors with descriptions from clients who avoided attempting suicide, an approach that is similar to those used in investigating mnemonics for suicide risk factors (Lester, McSwain, & Gunn, ; McGlothlin et al, ). Variables to consider when investigating the utility of SHORES include exploring client results in suicide behavior; in suicidal ideation; and in suicide‐related concerns, such as depression and hopelessness (McCabe, Garside, Backhouse, & Xanthopoulou, ). Clients who received counseling on SHORES can provide their ratings and perspectives on the intervention, including its helpfulness and their own sustained recall of the suicide protective factors (Stanley et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers can investigate the SHORES mnemonic by comparing its factors with descriptions from clients who avoided attempting suicide, an approach that is similar to those used in investigating mnemonics for suicide risk factors (Lester, McSwain, & Gunn, ; McGlothlin et al, ). Variables to consider when investigating the utility of SHORES include exploring client results in suicide behavior; in suicidal ideation; and in suicide‐related concerns, such as depression and hopelessness (McCabe, Garside, Backhouse, & Xanthopoulou, ). Clients who received counseling on SHORES can provide their ratings and perspectives on the intervention, including its helpfulness and their own sustained recall of the suicide protective factors (Stanley et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Many aspects of ASPIRE are adaptations of well‐established therapeutic approaches. Jobes et al 's () summary of cognitive therapy for suicide prevention, dialectical behaviour therapy, and Collaborative Assessment and Management of Suicidality along with McCabe's () systematic review that identified four brief intervention studies with varied theoretical foundations provides the evidence for these treatments and is the basis for the eclectic approach. ASPIRE includes the cognitive behaviour therapy (Brown et al , )‐based ‘Review Cycle’ which aims to reframe and modulate suicidal triggers, thoughts, feelings, and behaviours.…”
Section: Methodsmentioning
confidence: 99%
“…We will conduct searches across electronic databases (PsychINFO, MEDLINE, ERIC, Open Dissertations), and will manually search other relevant manuscripts (du Roscoät & Beck, 2013;Glenn et al, 2015;McCabe et al, 2018;Milner et al, 2015;Schleider et al, 2020;Fox et al, in preparation), for randomized controlled trials conducted in the past 50 years that evaluate effects of brief interventions on self-injurious thoughts and behaviors in young people (January 1, 1970 -January 31, 2020). Search terms will include: child, teen*, adolescen*, youth*, pediatric, college student, college students, young adult, or young adults; and suicid*, self-injury, self-harm, self-mutilation, self-cutting, cutting, self-burning, self-poisoning, NSSI, or SITB; and intervention, prevention, treatment, program, randomized, RCT, workshop, field trial, or training.…”
Section: Literature Searchmentioning
confidence: 99%
“…Evidence suggests it is worth taking a closer look at briefer mental health care options for SITBs in young people. For one, there is a clear demand, as calls for briefer SITB interventions are widespread in the suicide literature (Glenn et al, 2015;Lizardi & Stanley, 2010;McCabe et al, 2018;Stanley & Brown, 2012;Stewart et al, 2019). Further, brief interventions have shown promise for treating psychiatric problems in youth.…”
mentioning
confidence: 99%
See 1 more Smart Citation